2018
DOI: 10.1007/s12630-018-1221-0
|View full text |Cite
|
Sign up to set email alerts
|

Latent class analysis stratifies mortality risk in patients developing acute kidney injury after high-risk intraabdominal general surgery: a historical cohort study

Abstract: Among patients with AKI after high-risk general surgery, the preoperative comorbid state is associated with the time course of and survival after AKI. This knowledge can stratify mortality risk in patients who develop postoperative AKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The performed almost identically in predicting 30‐day mortality in the development and validation cohorts (AUROC 0.92, 95% CI 0.913–0.917 in the development cohort) and was well‐calibrated. Subsequently this method has been applied to the prediction of major postoperative complications 57,58 …”
Section: Resultsmentioning
confidence: 99%
“…The performed almost identically in predicting 30‐day mortality in the development and validation cohorts (AUROC 0.92, 95% CI 0.913–0.917 in the development cohort) and was well‐calibrated. Subsequently this method has been applied to the prediction of major postoperative complications 57,58 …”
Section: Resultsmentioning
confidence: 99%
“…Notably, LCA was used to explore AKI subphenotypes in critically ill patients with cardiovascular disease. LCA tends to be a popular method applied to clinical datasets to identify subphenotypes of diseases [20]. Both BIC criteria and entropy demonstrated that it was reasonable to divide AKI patients into 4 classes.…”
Section: Discussionmentioning
confidence: 99%
“…16 Using LCA, it is possible to categorize dementia based on the numbers of patient-and disease-specific factors rather than a single individual risk factor in predicting mortality. The LCA approach has been used in several previous studies investigating the homeless veteran population, 17 acute kidney injury, 18 and type 2 diabetes. 19 To the best of our knowledge, however, no study has used LCA to predict mortality risk in patients with dementia.…”
Section: Introductionmentioning
confidence: 99%